Pemberdayaan Usaha Kecil Mandiri melalui Pengembangan Strategi Penjualan dan Jaringan Distribusi di Kelurahan Siwalan Kecamatan Gayamsari Kota Semarang - Djoko Santoso; Paulus Wardoyo; Wyati Saddewisasi; Laurene Istiyawari (Fokus ABDIMAS, 2026)
The community service location was chosen for independent small businesses residing in Siwalan Village, Gayamsari District, Semarang City. This location was chosen because it is very close to the Semarang University campus. This area has potential for development, especially for small businesses that have been accommodated in the Jadoel Thematic Village, but have not yet seen success in business. This is due to fundamental problems: their limited ability to implement competitive sales strategies, inadequate utilization of distribution channels, and lack of product diversification, which has not yet developed effectively. The methods used in this community service include outreach and training, as well as evaluations. This activity will involve a question-and-answer session, allowing the team to assess the results of the community service. The results of this community service are targeted for publication in a journal and will help participants improve their entrepreneurial skills and increase sales in the future. Keywords: Independent small businesses, sales strategies and distribution channels, product labels, family income